Características de carcaça e da carne de animais zebuínos tratados com vitaminas D3 - Lara Macedo Bonfim Molina (2008)
Twenty Brahman steers grass fed were submitted to four treatments with oral vitamin D3 (0; 2,5; 5 e 10 x 106 UI) during ten days pre slaughter, to verify the effects of treatment on weight gain, carcass characteristics (dressing percent, percent of other components of carcass and lean cuts) and meat quality (pH, color, objective tenderness and cooking losses). At slaughter the steers aged 30 months and has 592 Kg. During the experimental period, the steers were weighted every two days, to obtain the average daily weight gain (ADWG). During slaughter carcass traits were measured and blood, muscle and liver samples were collected to analyze calcium, magnesium and phosphorus concentrations. After slaughter, temperature and pH of carcasses were measured on 3ª, 10ª e 24ª hour and Longissimus dorsi samples were collected to evaluate meat quality characteristics (color, objective tenderness and cooking losses). These samples were aged for 1, 14 and 28 days. There were no differences (P>0,05) between treatments for weight gain, quantitativecarcass characteristics and pH, color and cook losses. Concernig to tenderness, providing vitamin D3 was not effective to improve meat tenderness, in any of the studied times of aging.